Using eDNA to Identify the Dynamic Evolution of Multi-Trophic Communities Under the Eco-Hydrological Changes in River - Liang, Dong; Xia, Jun; Song, Jinxi; Sun, Haotian; Xu, Wenjin (Frontiers in Environmental Science, 2022)
As significant players in material cycling and energy flow, bacteria and eukaryotes play a vital role in the ecosystem. Nevertheless, the community dynamics of bacteria and eukaryotes in rivers and their responses to changes in ecological hydrology have not been studied thoroughly. Based on eDNA technology, this study investigated the bacterial and eukaryotic communities in the upper, middle and lower reaches of the Weihe River in different seasons. The seasonal variation and geographical distribution of bacterial and eukaryotic community structure showed significant heterogeneity. The selective theory well explained the response of microbial communities assembly to seasonal changes. Deterministic processes dominate microbial community assembly in the middle and lower reaches. Composition and metabolic potential of key functional genes of nitrogen and phosphorus cycling (nosZ, pqqB, pqqD, and pqqE) exhibited strong seasonal patterns and were significantly correlated with water physical and chemical properties. There were significant differences in molecular ecological networks in different periods (p < 0.05), with a gradually increasing trend in the complexity of the network from winter to summer. The keystone species (Hub) of the microbial food web in each season included microorganisms (Malikia), algae (Stephanodiscus), and invertebrates (Polyarthra). Structural equation modeling (SEM) results indicated that bacteria and invertebrates were important driving factors affecting the changes in community structures. In micro-food webs, both "bottom-up" (resources) and "top-down" (predation) forces strictly controlled the relationship between taxa. Nitrogen (N) and phosphorus (P) concentrations directly affected microorganisms, and there was a significant correlation between bacterial and eukaryotic groups and eco-hydrological variables (p < 0.05). Furthermore, we identified the taxon’s change point using threshold indicator taxa analysis (TITAN), quantitatively revealing the response thresholds of taxa to eco-hydrological changes.